Purified β‐glucans from the Shiitake mushroom ameliorates antibiotic‐resistant Klebsiella pneumoniae‐induced pulmonary sepsis. (1st October 2020) - Masterson, C.H.; Murphy, E.J.; Gonzalez, H.; Major, I.; McCarthy, S.D.; O'Toole, D.; Laffey, J.G.; Rowan, N.J.
Abstract: Bacterial infection remains the main cause of acute respiratory distress syndrome and is a leading cause of death and disability in critically ill patients. Here we report on the use of purified β‐glucan (lentinan) extracts from Lentinus edodes (Shiitake) mushroom that can reduce infection by a multidrug‐resistant clinical isolate of Klebsiella pneumoniae in a rodent pneumonia model, likely through immunomodulation. Adult male Sprague–Dawley rats were subjected to intra‐tracheal administration of K. pneumoniae to induce pulmonary sepsis and randomized to three groups; vehicle control (Vehicle, n = 12), commercial lentinan (CL, n = 8) or in‐house extracted lentinan (IHL, n = 8) were administered intravenously 1 h postinfection. Physiological parameters and blood gas analysis were measured, bacterial counts from bronchoalveolar‐lavage (BAL) were determined, along with differential staining of white cells and measurement of protein concentration in BAL 48 h after pneumonia induction. Use of IHL extract significantly decreased BAL CFU counts. Both CL and IHL extractions reduced protein concentration in BAL. Use of IHL resulted in an improvement in physiological parameters compared to controls and CL. In conclusion, administration of lentinan to treat sepsis‐induced lung injury appears safe and effective and may exert its effects in an immunomodulatory manner.